El Excentrico, 1967-03-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 5, 1967 [5 de marzo de 1967]. No volume or issue number. Cover has group photographs of members of the Santa Clara Chapter of the American GI Forum. They hosted the Black & White Coronation Ball at the Cabana Motor Hotel in Palo Alto on March 11th.